1998
DOI: 10.1023/a:1018811409538
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Since there are now several ways to treat symptomatic gallstone disease, one is able to select treatment on the basis of the patient's comfort, the practicability, effectiveness, and side effects of the technique, and the relative costs. In order to assess the present status of contact dissolution with methyl tert-butyl ether with regard to these aspects, the present enquiry reports the data of 21 European hospitals. Eight hundred three patients were selected for contact litholysis of cholesterol gallbladder s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Of these, MTBE is the only compound currently available. Although clinical studies have not reported critical toxicities of MTBE to date [4, 24, 25], several studies call into question the safety of MTBE. After administration, MTBE could be absorbed into the duodenum, leading to somnolence, nausea or vomiting [59, 1114], it can also be systemically absorbed, resulting in hemolysis and reversible kidney injury [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, MTBE is the only compound currently available. Although clinical studies have not reported critical toxicities of MTBE to date [4, 24, 25], several studies call into question the safety of MTBE. After administration, MTBE could be absorbed into the duodenum, leading to somnolence, nausea or vomiting [59, 1114], it can also be systemically absorbed, resulting in hemolysis and reversible kidney injury [26].…”
Section: Discussionmentioning
confidence: 99%
“…The first concern is high incidence of stone recurrence. In a study of enrolling 803 patients with gallstones who had received contact litholysis using MTBE, stone recurrence rate was about 40% in solitary stones and about 70% in multiple stones over 5 years [4]. Another challenge is to obtain the minimally invasive way of introducing the solvent into gallbladder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leuschner et al showed a dissolution rate of 96.6% in 120 patients with a low rate of complication and toxic side effects [ 14 ]. A larger survey in Europe of 803 patients from 21 institutions showed excellent dissolution rates with fewer side effects [ 11 ]. Common complaints included nausea, upper abdominal pain, duodenitis, and hemolysis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Common complaints included nausea, upper abdominal pain, duodenitis, and hemolysis [ 6 ]. Without proper ventilation, the odor did cause light headedness and nausea from the staff in one study [ 6 ] yet the odor from the European survey showed no issues from patient or staff [ 11 ].…”
Section: Discussionmentioning
confidence: 99%